2017
DOI: 10.1139/facets-2016-0061
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of parasitoid and parasitic wasps across a latitudinal gradient: Using public DNA records to work within a taxonomic impediment

Abstract: The diversity of insect parasitoids (Hymenoptera) has long been thought to be anomalous because it doesn't appear to increase rapidly with decreasing latitude. However, due to the presence of undiscovered cryptic species and the under-sampling of hyper-diverse tropical areas, such apparently anomalous gradients may, in fact, be artifacts of limited geographic and taxonomic sampling. We attempted to circumvent such taxonomic impediments by elucidating a diversity/latitude relationship for parasitoid wasps, usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 78 publications
(113 reference statements)
0
11
1
Order By: Relevance
“…Chalcidoidea species richness is higher in the tropics than in temperate zones [41]. Recent work shows that Ichneumonoidea may follow the same trend [42,43], challenging the idea that this taxa is more diverse at higher latitudes [44]. We did not identify wasps to the species level, but the abundance of wasps we observed in Chiapas may reflect the higher species richness of this taxon in the tropics.…”
Section: Natural Enemiescontrasting
confidence: 64%
“…Chalcidoidea species richness is higher in the tropics than in temperate zones [41]. Recent work shows that Ichneumonoidea may follow the same trend [42,43], challenging the idea that this taxa is more diverse at higher latitudes [44]. We did not identify wasps to the species level, but the abundance of wasps we observed in Chiapas may reflect the higher species richness of this taxon in the tropics.…”
Section: Natural Enemiescontrasting
confidence: 64%
“…Recent DNA sequencing studies of temperate tachinids have also revealed cryptic species, but at an apparently lower frequency (Pohjoismäki et al, 2016). Interestingly, a recent DNA barcode-based analysis of latitudinal patterns of diversity in Hymenopteran parasitoids failed to find evidence for greater hymenopteran parasitoid richness in the tropics (Eagalle and Smith, 2017).…”
Section: Limitations Of Available Datamentioning
confidence: 99%
“…In addition, a mass-barcoding study of Canadian insects found both Hymenoptera and Diptera more diverse than Coleoptera [87]. Moreover, other historically-accepted ideas about diversity of parasitoid hymenopterans have recently been questioned, including the apparent myth that parasitoids are one of only a few groups whose diversity decreases towards the tropics [88,89]. In any case, we hope this commentary results in a redoubled effort to understand and describe the ecology and natural histories of parasitoid wasps, including host ranges and cryptic host-associated diversity, such that estimates of P:H can be made for additional host genera.…”
Section: What Do Actual P:h Ratios Look Like In Nature?mentioning
confidence: 99%